Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Kinerja Guru di SMA Negeri 81 Jakarta Timur - Ghina Allya Pebriani; Adi Wibowo Noor Fikri; Christophorus Indra Wahyu Putra (Manajemen Kreatif Jurnal, 2024)
This research aims to find out how much influence leadership style and work discipline have on teacher performance at SMA Negeri 81 East Jakarta. The population in this study were all students in classes X1.1, X1.3, X1.7. The sampling method uses a Slovin sample, namely the entire population is used as a sample in distributing the questionnaire. The sample used in this research was 85 students. This research uses quantitative methods with multiple linear regression analysis, and hypothesis testing uses the t test and f test with a significance level of 5%. Based on the t test, Leadership Style has a significant effect on Teacher Performance and Work Discipline has a significant effect on Teacher Performance. And based on the f test, Leadership Style and Work Discipline influence Teacher Performance.